2014
DOI: 10.1111/jcpt.12225
|View full text |Cite
|
Sign up to set email alerts
|

SIMMEON-Prep study: SIMulation of Medication Errors in ONcology: prevention of antineoplastic preparation errors

Abstract: This study is the first demonstration of the successful application of a simulation-based learning tool for reducing errors in the preparation of injectable anticancer drugs. Such a program should form part of the continuous quality improvement of risk management strategies for cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…21 After training, the percentage of errors not identified significantly decreased to 20% (P-value = 0.04). 21 The current study extends these concepts into the field of radiation oncology.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…21 After training, the percentage of errors not identified significantly decreased to 20% (P-value = 0.04). 21 The current study extends these concepts into the field of radiation oncology.…”
Section: Discussionmentioning
confidence: 91%
“…20 Introducing medical errors into the clinical workflow has also been used to quantify the impact of training interventions. 21 In one study, medical errors were introduced into pharmacy technicians' instruction sheets, and the percentage of medication errors that were not identified was measured to be 48%. 21 After training, the percentage of errors not identified significantly decreased to 20% (P-value = 0.04).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such programs included from 11 to 96 healthcare providers, depending on the communication campaign and on whether participation was voluntary or obligatory (Table ). Studies were conducted in the context of daily activity, with deliberate insertion of patient identification errors, in the preparation of antineoplastic drugs by technicians, and in crisis scenarios such as management of acute anaphylaxis or septic shock . These 8 studies assessed drug preparation or administration error rates in nurses, pharmacy technicians, or anaesthesia trainees.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies demonstrated the efficacy of prevention tools such as awareness campaigns on iatrogenic risk associated with ME and the use of a bar code to detect patient identity error . Controlled trials used simulation programs to evaluate the superiority of certain professional practices compared to others: using prefilled syringes instead of preparation at the bedside in emergency situations, using checklists during the administration process to improve double‐checking, or mitigating error rates by reducing interruptions, such as request from a colleague or a question from a patient, while administering chemotherapy .…”
Section: Resultsmentioning
confidence: 99%